Penyuluhan Kesehatan Dengan Kejadian HIV/AIDS/AIDS Pada Remaja Di Wilayah Kerja Puskesmas Sorong Papua - Solihin, Solihin; Pannyiwi, Rahmat; Zaenal, Zaenal; Naka, Ali Syahid Bayau (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The problem of HIV/AIDS has become a serious phenomenon in the health sector. It cannot be denied that Indonesian people also have the same potential, although the triggering factors may vary in each region. This can be overcome by increasing public understanding regarding health literacy regarding HIV/AIDS prevention so that it does not spread further. The aim of this activity is to increase teenagers' knowledge about the importance of education about HIV/AIDS. The method used in this Community Service is outreach in the form of counseling to save the nation's next generation, especially teenagers. For this PKM activity, the target chosen is teenagers to be given in-depth education about prevention and combating HIV/AIDS. Participants in this activity were 24 teenagers. The evaluation of this activity was that the participants were able to understand the material presented, it was proven that the participants were motivated and enthusiastic in asking questions. The result of this activity was that there was an increase in participants' knowledge by following the socialization of the importance of HIV/AIDS education to teenagers, seen from the results of the pre-test carried out before the activity, 93.33% of participants had good knowledge and the results of the post-test were 100% of participants had good knowledge. In this way, it can be seen that there has been a change from not knowing to knowing the importance of HIV/AIDS education for teenagers.